Biocompatible nanomembranes based on PEGylation of cross-linked self-assembled monolayers - Meyerbröker, Nikolaus; Eck, Wolfgang; Zharnikov, Michael (Chemistry of materials, 2012)
We present the fabrication of freestanding, biocompatible, and ultrathin membranes on the basis of self-assembled monolayers (SAMs) of 4′-nitro-1,1′-biphenol-4-thiol (NBPT) on an Au(111) support. In the first step, NBPT SAMs were extensively cross-linked by exposure to low-energy electrons, resulting in a mechanically and thermally stable monolayer. Simultaneously, the terminal nitro groups of the NBPT molecules were converted to reactive amine moieties to which, in the second step, epoxy-functionalized poly(ethylene glycols) (PEG) were coupled. As far as the thickness of the coupled PEG overlayer exceeded ∼3 nm, as monitored by ellipsometry and X-ray photoelectron spectroscopy, the resulting assembly became protein-resistant, without losing this property after separation from the substrate as a freestanding membrane (third step). The use of such membranes as supports in transmission electron microscopy studies may improve essentially the resolution and structural reliability of such experiments in their specific application to sensitive biological targets. Whereas the ultimate thinness (<5 nm) and low atomic number character of the SAM-based membranes guarantee high imaging quality, their protein-repelling properties ensure the lack of protein denaturing.
Gesehen am 29.11.2018